Long‐term outcome of patients with gastric varices treated by balloon‐occluded retrograde transvenous obliteration. Issue 5 (May 2014) - Naeshiro, Noriaki; Aikata, Hiroshi; Kakizawa, Hideaki; Hyogo, Hideyuki; Kan, Hiromi; Fujino, Hatsue; Kobayashi, Tomoki; Fukuhara, Takayuki; Honda, Yohji; Ohno, Atsushi; Miyaki, Daisuke; Kawaoka, Tomokazu; et al.
Abstract Background and Aim To assess the short‐ and long‐term outcome of patients with gastric varices (GV) after balloon‐occluded retrograde transvenous obliteration (B‐RTO) by comparing bleeding cases with prophylactic cases. Methods Consecutive 100 patients with GV treated by B‐RTO were enrolled in this retrospective cohort study. We compared the technical success, complications, and survival rates between bleeding and prophylactic cases. Results Of 100 patients, 61 patients were bleeding cases and 39 patients were prophylactic cases. Technical success was achieved in 95% of bleeding case and in 100% of prophylactic case, with no significant difference between these groups (overall technical success rate, 97%). The survival rates at 5 and 10 years were 50% and 22% in bleeding case, and 49% and 36% in prophylactic case, respectively. There was also no significant difference (P = 0.420). By multivariate analysis, survival rates correlated significantly with liver function (hazard ratio 2.371, 95% CI 1.457–3.860, P = 0.001) and hepatocellular carcinoma development (HR 4.782, 95% CI 2.331–9.810, P < 0.001). The aggravating rates of esophageal varices (EV) were 21%, 50%, and 54% at 12, 60, and 120 months after B‐RTO. By multivariate analysis, aggravating rates significantly correlated with EV existing before B‐RTO (HR 18.114, 95% CI 2.463–133.219, P = 0.004). Conclusion B‐RTO for GV could provide the high rate of complete obliteration and favorable long‐term prognosis even in bleeding cases as well as prophylactic cases. Management of EV after B‐RTO, especially in coexisting case of GV and EV, would be warranted.